Architectural Responses to Extreme Heat: Designing For 50°C Cities of Punjab, Pakistan - Nijah Akram (Corresponding Author); Dr. Ayesha Mehmood Malik; Roma Mukhtar; Sania Shahid; Wasim Rafi Khan (`, 2026)
This research employed a mixed-methods approach to investigate architectural responses to extreme heat in Punjab, Pakistan's hottest regions experiencing temperatures exceeding 50°C. The study selected three severely affected cities-Multan, Bahawalpur, and Rahim Yar Khan-through purposive sampling based on recorded peak temperatures, heat wave frequency, and urban vulnerability. Data collection involved structured surveys administered to 180 residents to assess thermal discomfort levels, existing cooling strategies, and heat-related health impacts during Punjab's brutal summer months. The researcher conducted systematic observations using thermal imaging cameras and data loggers to measure surface temperatures, indoor thermal conditions, and heat stress patterns across 120 residential buildings constructed with traditional brick and concrete during May-July peak heat period. Semi-structured interviews with 35 residents explored their coping mechanisms, traditional cooling practices like roof watering and use of thatched shelters, and daily adaptations during extreme heat events. Additionally, the study engaged 12 local masons (rajis), 8 traditional builders, and 6 meteorological experts through focus group discussions to understand vernacular construction wisdom and indigenous cooling systems specific to Punjab's hot-arid plains. Climatic data analysis involved examining temperature records, dust storm patterns, and monsoon cycles from Pakistan Meteorological Department stations across southern Punjab. The researcher analyzed historical Punjabi architecture including thick-walled havelis, underground basements (tahkhanas), and ventilation towers through documentation studies. Four contextually appropriate design prototypes incorporating passive cooling, reflective materials, and traditional shading devices were developed and presented to communities through participatory workshops for validation and feedback. Keywords: Architectural Responses, Extreme Heat, Hottest Regions, Multan, Bahawalpur, And Rahim Yar Khan, Heat Wave Frequency